Chromatographic analysis and monitoring of fault gases in substation using ZIF-8 coated capillary column - Mao, Hua; Wang, Yan; Wang, Jie; Ma, Zeyao; Xia, Yalong; Zeng, Xiaoliang; Hu, Shihong; Lan, Xinsheng; Wang, Fangqiang; Zhou, Lin; Liu, Xuewen (Frontiers in Chemistry, 2025)
This study developed a ZIF-8-coated capillary gas chromatography column for the efficient separation of critical fault gases in electrical substations. By optimizing the carrier gas flow rate (3.5 mL/min) and column temperature (40°C), baseline separation of all components was achieved within 12 min, with resolution values of 0.8 and 3.8 for C3H6/C3H8 and C2H4/C2H6, respectively. The 3.4 Å molecular sieve pores of ZIF-8 preferentially retained larger hydrocarbons (e.g., C4H10) via size-exclusion effects, while its hydrophobic surface minimized non-specific adsorption of polar molecules like CO2. The low polarity of methylimidazole ligands ensured selective retention of nonpolar and weak polar gases. Remarkable reproducibility was demonstrated by retention time relative standard deviations (RSD) < 0.08% across 11 consecutive injections, confirming the coating’s mechanical stability. Coupled with high-temperature resistance and rapid analysis capabilities, this column provides a reliable tool for real-time substation gas monitoring, enabling early warning of faults (e.g., arcing, overheating) and intelligent diagnostics of insulation degradation.